THE PROHIBITION OF SITTING ON GRAVES IN THE PERSPECTIVE OF HADITH: A NORMATIVE AND ETHICAL STUDY IN ISLAMIC TRADITION - Alfi Syahrin Ramadhan; Uswatun Hasanah; Nurchalidin Nurchalidin (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2025)
This article examines the prohibition of sitting on graves from the perspective of the Prophetic Hadith by emphasizing historical, normative, and contextual dimensions. The study is motivated by contemporary phenomena in which graveyards are not only used as sites of pilgrimage but also function as spaces for social activities, such as commercial practices found in the Pocong Market in Palembang. Employing a qualitative descriptiveanalytical method, this research analyzes relevant Hadiths through the lenses of asbāb alwurūd, linguistic structure, meanings and wisdom, as well as scholarly debates regarding their legal implications. The findings indicate that the prohibition of sitting on graves isgrounded in strong Hadith transmission and aims to preserve human dignity after death and maintain the sanctity of burial sites. Scholarly differences concerning whether the ruling is ḥarām or makrūh stem mainly from contextual considerations and the intention behind the act, yet converge on the shared principle of honoring the deceased. This study concludes that the prohibition functions not merely as a legal injunction but also as an ethical and spiritual guideline that remains relevant for regulating proper conduct (adab) toward graves in contemporary Muslim society.